First person - Carmen Hernández-Ainsa (The Company of Biologists, 2022)
First Person is a series of interviews with the first authors of a selection of papers published in Disease Models & Mechanisms, helping early-career researchers promote themselves alongside their papers. Carmen Hernández-Ainsa is first author on ' Development and characterization of cell models harbouring mtDNA deletions for in vitro study of Pearson syndrome', published in DMM. Carmen is a research assistant in the lab of Eduardo Ruiz-Pesini at Universidad de Zaragoza, Zaragoza, Spain, investigating mitochondrial DNA deletions, pathological consequences and treatments through development of new in vitro models.